A barragem de Itaipu e suas fendas políticas. Do estudo pioneiro de Octávio Marcondes Ferraz ao projeto definitivo: a fronteira, os grupos políticos e as empresas que desenharam a forma definitiva da barragem (1962-1985) - Sessi , Valdir (2023)
The Brazilian political moment that culminated in the civil-military coup in 1964 coincided with a growing demand for electricity to feed the industrial park in the southeast region, which was booming. In this context, studies were carried out to increase the supply of energy for industries, having as main source, the Paraná River, on the border with Paraguay, in the state of Paraná. In addition to the hydroelectric potential, this border region (Guaíra/Foz do Iguaçu) stood out for being the focus of intense disputes in the field of diplomacy. Associated with this, there were also political movements among defenders of different architectural projects for the region that would contemplate only Brazil at one time, but at other times made the exploitation of the energy produced as part of Paraguay's law. In this sense, the objective of this research was to understand, through the theory of the social field, the pre-Itaipu negotiations for the execution of the construction, triggered by the office of Octavio Marcondes Ferraz (Usina Federal das Sete Quedas, 1962), but which ended in 1972, when the Italian-American multinational consortium presented other studies circumventing the negotiations and definitively ending the disputes in the region with the definitive creation of the binational project of Itaipu. Through documentary research, this study analyzed several documents available on the digital platform of the National Archive and documents from the Itaipu Documentation Center, aiming to answer our main question: is there a relationship between the building of Itaipu Binacional in Foz do Iguaçu (PR) and the mitigation of border conflicts with Paraguay? Furthermore, is there also a relationship between such attenuation and the benefits offered to Brazilian and Paraguayan contractors? The analyzed sources contributed to show the organizational network that made possible the interruption of the territorial dispute between Brazil and Paraguay that started in 1965 and the change of projects related to construction, preItaipu moment. The documents were instrumental in also demonstrating the working relationships during construction through the four different business axes involved in the construction of the plant. The results of the research also showed that the binational enterprise, following studies after Marcondes Ferraz, made it possible to seek bilateral agreements with Paraguay regarding border disputes, since the region was flooded by the artificial lake. In addition, the research clarified that even around this complex project model, numerous companies were employed in consortia, which, methodologically separated by axes. In this sense, the research presented some subjects acting in the civil-military dictatorship and in the Institute of Research and Social Studies (IPES) who had assured advantages acting as consultants in the accounting branch, and in the state administration itself. Thus, we consider that the research objectives and an answer to the initial questions were met. After that, the conclusions we reached are that Itaipu, through its cornerstone, went beyond being a geopolitical work. Its structural characteristic helped to provide a complex business organization that brought the construction to its end.